Prevalence of cardiac arrhythmias among patients undergoing chronic hemodialysis - O. V. Likhachev-Mishchenko; A. A. Kornienko; N. A. Kornienko; E. G. Kadyan; L. A. Khaisheva; S. V. Shlyk (Российский кардиологический журнал)
Aim. To evaluate the prevalence of arrhythmias in patients undergoing chronic hemodialysis, to characterize the arrhythmia types in relation to the dialysis procedure and to determine their relationship with clinical findings and echocardiographic characteristics.Material and methods. The study involved 152 patients with kidney failure undergoing chronic hemodialysis. All patients underwent an assessment of dialysis parameters, collection of clinical data, and 48-hour Holter monitoring. In addition, 93 patients underwent an echocardiography with an assessment of left ventricular (LV) mass index, LV ejection fraction, left atrial (LA) volume index, E/e’, cardiac output and preload, which was defined as increased LV filling pressure (E/e’ >12) and LA enlargement (LA volume index >30 ml/m2).Results. Among the 152 examined patients, premature supraventricular and ventricular contractions (PVCs) were observed in almost all patients, while 41% had paroxysmal supraventricular tachycardia. Clinically significant arrhythmias included persistent atrial fibrillation (AF) in 8,6% of patients, paroxysmal AF in 3,9%, nonsustained ventricular tachycardia in 19,7%, bradycardia in 4,6%, second-degree atrioventricular block in 1,3% and third-degree atrioventricular block among 2,6%. PVCs were more common on dialysis days, while tachyarrhythmias were more common during dialysis and in the immediate post- dialysis period. Older age (odds ratio (OR) 10 years older, 1,53; 95% confidence interval (CI): 1,15-2,03; P=0,003), lower cardiac output (OR 1 L/min more, 0,66; 95% CI: 0,44-1,00; P=0,05) were independently associated with clinically relevant arrhythmias.Conclusion. In patients on chronic hemodialysis, older age, increased preload and lower cardiac output are independently associated with clinically relevant arrhythmias. In addition, a positive association between increased LV mass index and AF episodes has been demonstrated. Lower cardiac output had positive correlation with AF and ventricular arrhythmias.